2014
DOI: 10.1002/smi.2575
|View full text |Cite
|
Sign up to set email alerts
|

Having the Time of Their Life: College Student Stress, Dating and Satisfaction with Life

Abstract: A cross-sectional design based on the family ecosystem framework was used to examine how students' time spent engaging in social interactions and personal behaviours was related to dating, stress and satisfaction with life. The data were extracted from the Parental Indulgence of Emerging Adults study and consisted of 534 students at a southeastern university. The findings indicated that the amount of time involved in non-verbal social interactions, such as texting and social networking, along with solitary act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 38 publications
1
19
0
3
Order By: Relevance
“…Existen pues, diferentes factores que afectan la satisfacción con la vida, como el) estrés, la conexión social y el locus de control, etc. (Coccia y Darling, 2014;Dave et al, 2011). De acuerdo con Diener y Chan (2011) las evaluaciones del bienestar subjetivo de las personas incluyen las reacciones emocionales a los eventos, sus estados de ánimo y los juicios que se forman sobre la satisfacción personal, con la vida y en los diferentes dominios tales como el matrimonio y el trabajo.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Existen pues, diferentes factores que afectan la satisfacción con la vida, como el) estrés, la conexión social y el locus de control, etc. (Coccia y Darling, 2014;Dave et al, 2011). De acuerdo con Diener y Chan (2011) las evaluaciones del bienestar subjetivo de las personas incluyen las reacciones emocionales a los eventos, sus estados de ánimo y los juicios que se forman sobre la satisfacción personal, con la vida y en los diferentes dominios tales como el matrimonio y el trabajo.…”
Section: Introductionunclassified
“…El bienestar es pues, un tema importante de investigación en varias disciplinas, lo que refleja el creciente reconocimiento de su gran valor en los principales dominios de la vida. Por lo tanto se considera trascendente explorar la composición factorial de la Escala de Satisfacción con la Vida de Diener en universitarios mexicanos, ya que éstos se enfrentan a presiones en todos los elementos de su entorno; y la manera en que se acercan a su entorno sociofísico puede influir en su satisfacción general con la vida (Coccia y Darling, 2014). Por otro lado, la importancia intercultural de la felicidad y la satisfacción se puede inferir de su aparición en discusiones filosóficas a través de muchas tradiciones culturales, y se ha encontrado que los componentes del bienestar psicológico correlacionan en la mayoría de las culturas, dichas similitudes interculturales son relevantes porque resaltan nuestra humanidad común (Tov y Diener, 2013).…”
Section: Introductionunclassified
“…Thinking that university students' satisfaction with life is important caused that the researches on this matter has increased in recent years (Yetim, 2003;Kümbül-Güler and Emeç, 2006;Gündoğar et al, 2007;Tuzgöl, 2007;2010;Ceçen, 2008;Sahranç, 2008;Ozgur et al, 2010;Aydıner, 2011;Ergin et al, 2011;Civitçi, 2012;Deniz et al, 2012;Kabasakal and Uz-Baş, 2013;Recepoğlu, 2013;Uğurlu, 2013;Ardahan, 2014;Gülcan and Nedim-Bal, 2014;Özgüngör, 2014;Demir-Güdül, 2015;Ertekin-Pınar et al, 2015;Özdemir and Dilekmen, 2016;Bakan and Güler, 2017;Elkin, 2017;Hırlak et al, 2017;Yıldız and Karadaş, 2017). In literature review, although there are studies on subjects such as stress and satisfaction with life (Civitci, 2015;Kaya et al, 2015;Coccia and Darling, 2016) academic stress, satisfaction with life and achievement motivation (Karaman et al, 2018) among university students; it is seen that the relationships between satisfaction with life and coping (Deniz, 2006;Odacı and Cıkrıkçı, 2012) satisfaction with life and motivation (Demir-Güdül, 2015) coping and motivation are investigated in a limited numbed of studies. In addition, studies which investigate the intermediary role of ways of coping with stress in the relationship between the satisfaction with life and motivation of university students could not be found in the literature review.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that college student stress levels have steadily increased in the last 5 years with 33.8% of students reporting anxiety levels that negatively impact school function (Coccia & Darling, 2016;Maykrantz & Houghton, 2018). School-related stress and anxiety have been found to be doubly problematic in graduate health care students seeking careers in medicine, dentistry, nursing, and physical and occupational therapy (Barbosa et al, 2013;McConville et al, 2017;van der Riet et al, 2018).…”
mentioning
confidence: 99%
“…School-related stress and anxiety have been found to be doubly problematic in graduate health care students seeking careers in medicine, dentistry, nursing, and physical and occupational therapy (Barbosa et al, 2013;McConville et al, 2017;van der Riet et al, 2018). Studies have found that 75% to 85% of graduate health care students report moderate stress levels while 10% to 12% report severe anxiety (Bruffaerts et al, 2018;Coccia & Darling, 2016;Galante et al, 2018). Stressors commonly emerge from financial problems and loan debt; juggling school and family responsibilities; transitioning from a moderately challenging undergraduate experience to intensive graduate work with increased workload and knowledge acquisition demands; and interacting, perhaps for the first time, with severely ill patients (Ahmad et al, 2017;Farquhar et al, 2018).…”
mentioning
confidence: 99%